A health impact assessment model for environmental changes attributable to development projects. Issue 8 (1st August 2002) - McCarthy, M; Biddulph, J P; Utley, M; Ferguson, J; Gallivan, S
Abstract : Study objective: European Union legislation requires large industrial and civil development projects to undergo environmental impact assessment. The study objective was to identify environmental health risk estimates for these developments from the epidemiological literature and to develop, and apply these within, a mathematical health impact assessment model. Design and results: In the UK, good practice guidelines have set out environmental issues to be considered in development projects, but little attention is given to direct health effects. Broad quantifiable risks were identified for four—air, chemicals, noise, and road traffic—of 14 standard environmental effects. A mathematical model was constructed that is based on people moving between different health states over their lifetime. Age related hazard functions are applied to cause specific measures of mortality and morbidity. A hypothetical example for a development creating air and chemical pollutants is given. Conclusions: A mathematical model applying epidemiological risks to an exposed population can provide quantification of environmental health effects. The approach may in future find application during project development, and by public health regulatory authorities for environmental health impact assessment.